Endocrine function and morphological findings in patients with disorders of the hypothalamo-pituitary area: a study with magnetic resonance. Issue 11 (November 1990) - Cacciari, E; Zucchini, S; Carlà, G; Pirazzoli, P; Cicognani, A; Mandini, M; Busacca, M; Trevisan, C
Abstract : Evaluation of the sellar area was performed with magnetic resonance imaging in 101 patients (age range 0.8-27 years) with hypopituitarism, isolated diabetes insipidus, hypogonadotrophic hypogonadism, and central precocious puberty. The hypopituitary patients (n = 70) included multiple pituitary deficiency (n = 23), pituitary deficiency with diabetes insipidus (n = 5), and isolated growth hormone deficiency (n = 42). The patients with multiple pituitary deficiency showed pathological morphological findings in all cases, with stalk and posterior lobe always involved. The group with associated diabetes insipidus had abnormal stalk in four of five cases and posterior lobe not visible in all cases. Only five of 42 (12%) patients with isolated growth hormone deficiency had abnormalities of the sellar area. In two out of four patients with isolated diabetes insipidus posterior lobe was not seen. All patients with hypogonadotrophic hypogonadism (three with Kallmann's syndrome, one Prader-Willi syndrome, and two idiopathic hypogonadism) appeared normal. In precocious puberty (n = 21) the three patients with onset of symptoms before age 2 years exhibited a hypothalamic hamartoma, whereas in the others with onset of puberty between age 2 and 7 the magnetic resonance image was normal in 17 of 18 patients. The probability of finding a pathological magnetic resonance image was considerably high in our patients with multiple pituitary deficiency, isolated diabetes insipidus, and precocious puberty with very early onset of symptoms. On the contrary, purely functional abnormality is suggested in most patients with isolated growth hormone deficiency, hypogonadotrophic hypogonadism, and precocious puberty with later onset of symptoms.